Digital marketing focused on the use of seo tools on web pages and social networks of the hotel sector in Tulcan. - Enríquez Herrera, Jhonny; Revelo Valenzuela, Carlos (SATHIRI, 2020)
The present document highlights the importance of information technology at present and its trends in the information society, emphasizing a tendency that is gaining strength within the organizations and institutions in general called Digital Marketing; in addition, an analysis was made of this trend, particularly focused on the management of Web pages and social networks within the hotel sector of the city of Tulcán, province of Carchi, Ecuador. considering this, it was used the type of mixed research, which according to its approach allowed us to collect, analyze and link quantitative and qualitative data with the purpose of knowing the management and status of Web pages and social networks in the hotels in the city. The results of the investigation, allowed to guide the use of some SEO tools online, which are useful for carrying out audits on all kinds of information contained in a Website or Social Network in relation to the target audience, which allows to identify corrective measures to certain established parameters, conduct comparative analyses with similar pages and establish strategies to improve the corporate image and content of institutional digital information in general.
Keywords: Digital marketing; Social Network; SEO; Audit; Corporate image